Project Management in the Universidad de Oriente: Improvement of the Ex-Antes Evaluation - Yilian Rodríguez-Clavijo; Liliana Gómez-Luna; Norma Rafaela Hernández-Rodríguez; Dainelis Cabeza-Pullés (Anuario Facultad de Ciencias Económicas y Empresariales, 2017)
The objective of this study was to demonstrate the importance of ex-ante evaluation as a tool for the management of science and innovation projects at the Universidad de Oriente. For the theoretical analysis we used the methods analysis - synthesis and historical - logic. In the empirical analysis, participant observation, work with a team of experts and brainstorming were used as techniques and tools. The methodological design of the evaluation was defined according to four aspects established by the Organization for Economic Cooperation and Development: field, purpose, criteria and organization. The results of the application of the methodology are presented to the projects to selected projects; which allowed diagnosing the quality of the projects, the areas with the most deficiencies, as well as the aspects that limit the design of the proposals.